2018
DOI: 10.18502/kss.v3i5.2330
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Living Opportunities and Challenges for Low-income People in Southeast Asia Case of Indonesia

Abstract: With limited land available, it is a fact and unavoidable that the house should be built vertically. When countries in Europe have started to organize it long enough since the end of the World War II in the 1950s, many states in Southeast Asia can be said to be relatively newer in developing this vertical residential building. Indonesia, for example, began to construct since the 1970s. However, it was in the 1990s that this type of housing was largely built and characterized by a type of luxurious apartment co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Commercial spaces for selling goods or foods provided in Rusunawa are limited and the design is generic for any type of home industry or economic activity. A study by Swasto (2018) found that many residents had difficulty in continuing their previous business and continuing their work habits since the living space and the commercial spaces in the Rusunawa had no flexibility and compatibility to support their business and work habits. Although the design of Rusunawa does not serve and empower the economic needs of its residents, a recent study by Subagijo and Suhartono (2018) discovered that 28% of residents of the Rusunawa in Kutobedah Malang utilized part of their living units, the area around stairs and corridor, as their economic activity space.…”
Section: Introductionmentioning
confidence: 99%
“…Commercial spaces for selling goods or foods provided in Rusunawa are limited and the design is generic for any type of home industry or economic activity. A study by Swasto (2018) found that many residents had difficulty in continuing their previous business and continuing their work habits since the living space and the commercial spaces in the Rusunawa had no flexibility and compatibility to support their business and work habits. Although the design of Rusunawa does not serve and empower the economic needs of its residents, a recent study by Subagijo and Suhartono (2018) discovered that 28% of residents of the Rusunawa in Kutobedah Malang utilized part of their living units, the area around stairs and corridor, as their economic activity space.…”
Section: Introductionmentioning
confidence: 99%